The Influences of Content Creation and Community Building on Purchase Decision during COVID-19: A Case Study of Sociolla - Putri, Nadiyah Asmaranti Anita; Pasaribu, Pananda (Journal of Business, Management, and Social Studies, 2022)
This study aims to ascertain the influence of social media marketing via Instagram, which includes content creation and community building, on purchase decision in Sociolla during the pandemic. This study collected primary data from respondents via questionnaires. The respondents were 101 people with customers who became Sociolla followers and made online purchases on Sociolla during the COVID-19 pandemic. SPSS was used to analyze the data in this analysis. Analytical techniques include multiple linear regression analysis, the t test for partial hypotheses, the F test for simultaneous hypotheses, and the coefficient of determination (R²). This study found that content creation and community development had a significant positive effect on purchase decision. The partial results (t test) indicate that the variables relating to content sharing most influence purchase decision. While concurrently (F test) demonstrates that content creation and community building have a significant effect on purchasing decisions. Although the relationship between community building and purchase decision has been examined in past research, the specific relationships examined in this study in comparison with the content creation-purchase decision relationship has not yet been previously investigated using a local cosmetic brand followers in Indonesia.